PENGARUH PENGGUNAAN SHOPEE PAYLATER, LITERASI KEUANGAN DAN GAYA HIDUP TERHADAP PERILAKU KONSUMTIF MAHASISWA - Girsang, Asrhy Grisara; Dewi, Made Heny Urmila (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 12 (2024): Vol.13.No.12. DESEMBER 2024 [831-914]DO - 10.24843/EEP.2024.v13.i12.p01, 2025)
Consumption activities refer to the use of income to obtain various goods or services to meet human needs. The top priority in consumption activities is fulfilling basic needs or primary needs, which are needs that are very essential for humans. As is done by the general public or families, students are also involved in daily economic activities, including in the aspect of consumption. At this time, many students are starting to shift the use of their monthly pocket money to fulfill consumption not only of necessities but also to consume what they want such as buying clothes, accessories or other current trend symbols. This indicates that students behave consumptively. Consumptive behavior refers to excessive consumption actions without paying attention to awareness of the needs that are actually needed. Someone who shows consumptive behavior tends to prioritize their desires and personal satisfaction rather than considering their needs. This study aims to investigate the impact of using Shopee PayLater, financial literacy, and lifestyle on student consumptive behavior through a survey method. The object of this research is undergraduate students of the Faculty of Economics and Business, Udayana University who use the paylater feature on the Shopee application. The sample of this study amounted to 210 respondents from the Faculty of Economics and Business, Udayana University. The analytical method used in this study is descriptive analysis and multiple regression analysis. The study shows that thetuse of Shopee PayLater does nottaffect student consumptivetbehavior. Higher financial literacy leads to less consumptive behavior, but a lifestyle that values material goods and trends promotes more consumptive habits.